Assessment of the Hormetic Effect of Arsenic on Growth and Physiology of Two Cultivars of Maize (Zea mays L.) - Piršelová, Beáta; Galuščáková, Ľudmila; Lengyelová, Libuša; Kubová, Veronika; Jandová, Vilma; Hegrová, Jitka (Plants (Basel, Switzerland), 2022)
Although growth stimulation at low arsenic doses was observed in several plants, few studies have focused on this phenomenon in more detail. The effects of different concentrations of arsenic (0-50 mg kg-1 of soil: As0-As50) on the growth and selected physiological parameters of two maize cultivars (Zea mays L. cvs. Chapalu and MvNK 333) were tested. Cultivar MvNK 333 manifested a generally higher tolerance to As than cv. Chapalu, which may be related to the lower content of As in the tissues. The highest stimulatory effect of As was recorded at doses of As1 and As2 (cv. Chapalu), and at the As5 dose (MvNK 333), there was an increase in shoot elongation, biomass, and relative water content (RWC), as well as the content of photosynthetic pigments. The stimulatory effect of lower doses of As apparently represents an adaptation mechanism that is associated with water content regulation in the given conditions. The stomata of the studied cultivars were involved in this regulation in different ways. While cv. Chapalu exhibited increased numbers of stomata on both sides of leaves, cv. MvNK 333 instead responded to the given conditions with decreased stomata size. Although hormetic manifestations closely related to changes in stomatal number and size were observed, a typical stomatal hormetic response was not observed in the given range of As doses.
Keywords: arsenic; maize; growth; stomata; water balance; photosynthesis